Risk Characterization of the Armenian Population to Nickel: Application of Deterministic and Probabilistic Approaches to a Total Diet Study in Yerevan City - Pipoyan, Davit; Stepanyan, Seda; Beglaryan, Meline; Mantovani, Alberto (Biological trace element research, 2023)
Nickel (Ni) is a widespread metal that occurs in food and drinking water from both natural and anthropogenic sources. Oral exposure to Ni can induce a variety of adverse effects; the European Food Safety Authority established a tolerable daily intake (TDI) of 13 μg/kg bw and a lowest-observed-adverse-effect level (LOAEL) of 4.3 μg/kg bw to assess the risk of allergic reactions upon acute exposure. This study, the first conducted in Armenia, aimed to assess the dietary exposure of the adult Yerevan population (1272 subjects of both sexes) to Ni in a total diet study (TDS). Detection of Ni was carried out using atomic absorption spectrometry. To determine food consumption values, a 24-h recall survey was used. Following the K-means clustering test, two clusters were determined for food product intake. For the risk characterization of acute oral exposure, the margin of exposure (MOE) was calculated using both deterministic and probabilistic (Monte Carlo method) approaches. The average total exposure was 4.396 μg/kg bw, with limited influence by age and gender. The main contributors were “fruits and vegetables” followed by “bread and flour-based products”: the total intake would be 5.11 μg/kg bw for a woman with high consumption of fruits and vegetables. Hence, the estimated chronic dietary exposure was below the TDI, irrespective of age and gender groups, and including high consumers. However, acute oral exposure estimates led to MOE values of less than 30 for most food products, indicating potential health concerns for Ni-sensitized individuals. The Monte Carlo approach indicated that the probability of occurrence of MOE lower than 30 was very high in the case of beef/veal, pork and chicken meat, eggs, and fish, alongside vegetable sources such as buckwheat, tomato, watermelon/melon, and potatoes. The findings prompt an investigation of Ni sources in the target foods in the Caucasus area.